Uncertainty and Firms' Labour Decisions. Evidence from European Countries - Marta Martinez-Matute; Alberto Urtasun (Institute of Labor Economics (IZA), 2020)
Uncertainty affects employers' decisions on labour workforce, as it does on capital. We exploit differences on how firms adjust their labour work-force when uncertainty increases. Using data from the Wage Dynamic Network Survey for 25 European countries, we first construct, opposite to usual aggregate indicators, a set of uncertainty indicators exploiting firms' microeconomic environment. We combine variability from the country, sector and size of the firm. Secondly, we investigate the effect of uncertainty on firms' strategies to adjust labour through hirings and rings. Results reveal that firms reduce hiring decisions and recur to individual layos more frequently when uncertainty increases. An increase of one point in the uncertainty indicator increases the probability of having frozen hiring in between 21% to 39%. We also find more significant effects when firms are facing credit constraints and labour adjustment costs are higher.
Keywords: D22; D81; J21; J23; 330; uncertainty; labour adjustment; firms' labour decisions; freeze hirings; layoffs